2007
DOI: 10.1161/01.atv.0000256468.95403.6f
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Peripheral Artery Intima Thickness From Childhood to Seniority

Abstract: Background-Using new, very high-resolution ultrasound biomicroscopy, we examined the thickness of artificial layers of silicone and intima thickness (IT) of radial and anterior tibial arteries in healthy subjects and in patients with vascular disease. Methods and Results-Silicone layers of varying thicknesses and mesenteric artery specimens obtained from 18 patients undergoing colectomy were measured by both ultrasound biomicroscopy (55 MHz) and morphometry. There was high correlation (rϾ0.9; PϽ0.0001) between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 18 publications
5
91
3
Order By: Relevance
“…Because the forearm has been exclusively used as a model for studying vascular function, it has become common to extrapolate the findings obtained from this vascular bed to the rest of the body. However, the heterogeneity between the upper and lower limbs in adrenoceptor-mediated control in both muscle and skin blood flow should be considered in the evaluation of vascular function, because morphophysiological changes in the forearm vasculature resulting from a pathological state or aging do not always parallel those observed in the lower extremities (27,28,32).…”
Section: Discussionmentioning
confidence: 99%
“…Because the forearm has been exclusively used as a model for studying vascular function, it has become common to extrapolate the findings obtained from this vascular bed to the rest of the body. However, the heterogeneity between the upper and lower limbs in adrenoceptor-mediated control in both muscle and skin blood flow should be considered in the evaluation of vascular function, because morphophysiological changes in the forearm vasculature resulting from a pathological state or aging do not always parallel those observed in the lower extremities (27,28,32).…”
Section: Discussionmentioning
confidence: 99%
“…with a Visualsonics MS550D and a 22 to 55-MHz probe (VisualSonics Inc., Toronto, Canada), a high-resolution ultrasound system with a spatial resolution of 30 to 50 μm. [6][7][8] At baseline, an estimated puncture site with adequate radial pulsation was marked. The area was photographed and digitally stored as a reference for the evaluation at follow-up ( Figure I in the Data Supplement).…”
Section: Ultrasound Evaluationmentioning
confidence: 99%
“…Intima thickness was defined as the distance from the leading edge of the lumen-intima interface to the interface between intima and media and separately measured as in previous report using the same technology. 8 The media thickness was calculated by subtracting the intima thickness from the intima-media thickness.…”
Section: Echographic End Pointsmentioning
confidence: 99%
“…However, it is worth mentioning the different age of studied population (oldest in the last two studies), the different protocol measurement of IMT in the carotid tree that could be responsible for discrepancy of results. Indeed, it is well understood an age-dependent increase of IMT value [92], higher in elderly people, as like a different reproducibility and accuracy of IMT measurement when performed in different carotid anatomical sites and/or when calculated in different manner. Particularly, the ARIC study reported IMT value as combined measurement of the far wall (with respect to the transducer) of the common and internal carotid artery whereas the authors of Rotterdam study used a different index, as like the mean of the distal 1 cm of both common carotid arteries.…”
Section: Intima-media Thickness (Imt) Measurementmentioning
confidence: 99%